Knowledge of, attitudes toward and practices of ethics of war of the officers and soldiers of the Zambia Army - Sikazwe, William; Kalula, Evance; Kazonga, Eustarckio (Scientia Militaria - South African Journal of Military Studies, 2022)
Since the end of the world wars, the demise of the Cold War and the end of liberation wars in Africa, the changing character of warfare has given birth to uncertainties about how states will respond to acts of aggression in the face of ethics of war, or the moral rules of war. It has become difficult for states to conduct permissible self-defence and other-defence against non-state actors or sub-state groups, which do not have a sovereign (political and territorial integrity) to protect. In the face of this reality, it is not known how much knowledge military personnel world over have on ethics of war, what their attitude towards ethics of war is, and how they practice these ethics of war during war and operations other than war. Research was therefore conducted to assess knowledge of, attitudes toward and practices of the ethics of war of officers and soldiers of the Zambia Army. A mixed method research was undertaken using explanatory sequential approach. A sample of 420 participants was drawn from officers and soldiers serving in the Zambia Army. Questionnaires were used to collect quantitative data, while focus group discussions and interviews were undertaken to collect qualitative data. The findings from the focus group discussions and interviews provided depth and understanding about how the officers and soldiers felt about ethics of war. The findings of focus group discussions and interviews also helped to explain the findings from the quantitative data. Quantitative data were analysed at two levels. The first level of analysis comprised descriptive statistics in the form of frequency distribution tables, means and percentages. The second level involved inferential statistics by applying the chi-square test in order to determine the relationship, if any, between the independent variables and the dependent variables using the Statistical Packaging for Social Sciences. Further, the research used Spearman’s rank correlation coefficient to measure the strength and direction of association between two ranked variables. Analysis of qualitative data begun during the data collection exercise by arranging the field notes according to salient themes in relation to the objectives. This was followed by pinpointing, examining and recording patterns within the data collected. The conclusion of the study showed that, at the time, the majority of the Zambia Army officers and soldiers were reasonably acquainted with the knowledge of ethics of war. The study further concluded that Zambia Army officers and soldiers held very strong and positive attitudes towards the ethics of war at the time. In addition, the officers and soldiers also widely accepted and supported the ethics of war, as they considered them beneficial. It was evident from the research that the Zambia Army soldiers and officers practiced the ethics of war extensively and regularly during both local and international operations. However, more needs to be done to increase knowledge levels.